2018
DOI: 10.3332/ecancer.2018.838
|View full text |Cite
|
Sign up to set email alerts
|

Supportive care needs of multicultural patients with cancer in the United Arab Emirates

Abstract: Despite the high prevalence of cancer in the Middle East, there is limited published data reporting the needs of cancer patients in this region of the world. The purpose of this study is to assess the unmet supportive care needs of oncology patients in the United Arab Emirates (UAE). From December 2014 to December 2016, a cross-sectional survey of cancer patients was conducted at a large tertiary care hospital and an oncology referral centre in the UAE, using a validated Arabic translation of the supportive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Notably, assessment of information needs of patients with breast cancer should account for cultural factors. For example, in Nair et al (2018), an assessment of information needs in Chinese women with breast cancer revealed an unmet need for information related to sexuality and negative body image. However, the low need for this information may have been related to the tendency to avoid discussion of issues related to sexuality and body image in Asian culture.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, assessment of information needs of patients with breast cancer should account for cultural factors. For example, in Nair et al (2018), an assessment of information needs in Chinese women with breast cancer revealed an unmet need for information related to sexuality and negative body image. However, the low need for this information may have been related to the tendency to avoid discussion of issues related to sexuality and body image in Asian culture.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, previous studies conducted in other Islamic countries like Malaysia and the UAE have similarly found the sexuality domain to be ranked low in terms of priority compared to other domains. 8,16 As in other conservative communities, Omani women are often embarrassed and reluctant to explore their sexual needs and concerns with healthcare professionals, as such topics are considered taboo due to cultural norms. 27 Furthermore, it is not considered routine practice to assess the sexual wellbeing of cancer patients in Oman.…”
Section: Discussionmentioning
confidence: 99%
“…A previously validated Arabic version of the 34-item Supportive Care Needs Survey-Short Form (SCNS-SF34) was used to collect data regarding the respondents' unmet supportive care needs. 8 The original SCNS-SF34 is a validated instrument used as part of routine cancer care to measure cancer patients' perceived unmet supportive care needs across five domains, including psychological (10 items), health system and information (8 items), patient care and support (6 items), physical and daily living (5 items), sexuality (2 items) and other needs (3 items). 15 Originally, it was intended that the data were to be collected using a paper-based questionnaire; however, as a result of the ongoing coronavirus disease 2019 (COVID-19) pandemic, research assistants were prohibited from entering SQUH and having direct contact with patients in order to minimise the risk of transmission.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations